TiO2 and ZnO as Advanced Photocatalysts for Effective Dye Degradation in Textile Wastewater - Barbara Simončič; Dominika Glažar (Tekstilec, 2023)
Textile wastewater, which consist of a complex mixture of synthetic dyes and other organic and inorganic compounds derived from various wet chemical textile processes, can have a harmful effect on the environment; therefore, it must be properly treated before being discharged into municipal wastewater treatment plants and natural water bodies. In this scientific review, the main physical, chemical and biological processes for the removal of dyes from textile wastewater are presented, focusing on photocatalysis, which is a promising advanced oxidation process. The mechanism of photocatalysis is described and the methods used to determine the efficiency of photocatalytic degradation of dyes are presented. Recent studies involving single photocatalytic treatments of real textile wastewaters in the presence of TiO2 and ZnO as catalysts are presented. The advantages of combined processes of photocatalysis in conjunction with other chemical, physical and biological treatments to increase the efficiency of wastewater treatment are discussed. Accordingly, photocatalysis combined with H2O2, photocatalytic ozonation, a hybrid system of photocatalysis and membrane filtration, and coupled photocatalytic-biological processes are described.